Predictors of long-term outcomes in patients treated with riociguat for pulmonary arterial hypertension: data from the PATENT-2 open-label, randomised, long-term extension trial. Issue 5 (May 2016) - Ghofrani, Hossein-Ardeschir; Grimminger, Friedrich; Grünig, Ekkehard; Huang, Yigao; Jansa, Pavel; Jing, Zhi-Cheng; Kilpatrick, David; Langleben, David; Rosenkranz, Stephan; Menezes, Flavia; Fritsch, Arno; Nikkho, Sylvia; et al.
Summary: Background: Pulmonary arterial hypertension is a chronic disease associated with poor long-term outcomes. Identifying predictors of long-term outcome in pulmonary arterial hypertension is important to assess disease severity and guide treatment. We investigate associations between efficacy parameters and long-term outcomes in patients with pulmonary arterial hypertension receiving riociguat in the PATENT-2 study. We also present safety and efficacy data from the final data cutoff of PATENT-2, where most patients had received at least 2 years of riociguat treatment. Methods: Eligible patients from the PATENT-1 study entered the PATENT-2 open-label extension, which will continue until all patients transition to the commercial drug. All patients received riociguat individually adjusted to a maximum dose of 2·5 mg three times a day. The primary endpoint was safety and tolerability, assessed with recording adverse events, serious adverse events, discontinuations, and deaths; exploratory assessments included 6-min walking distance (6MWD), WHO functional class, N-terminal prohormone of brain natriuretic peptide (NT-proBNP)concentrations, Borg dyspnoea score, health-related quality of life (EQ-5D score), survival, and clinical worsening-free survival. Association between efficacy parameters and long-term outcomes was assessed using Kaplan-Meier analyses and a Cox proportional-hazards regression model. PATENT-2 is registered atClinicalTrials.gov, numberNCT00863681 . Findings: 396 patients entered PATENT-2, of whom 197 patients were receiving riociguat monotherapy and 199 were receiving riociguat in combination with endothelin receptor antagonists or prostanoids, or both. A significant association was noted between 6MWD, NT-proBNP concentration, and WHO functional class and overall survival at baseline (p=0·0006, 0·0225, and 0·0191, respectively), and at follow-up (p=0·021, 0·0056, and 0·0048, respectively). Riociguat was well tolerated in PATENT-2. Serious adverse events were recorded in 238 (60%) of the total population, and 45 (11%) patients discontinued treatment because of an adverse event. Improvements in 6MWD, WHO functional class, and NT-proBNP concentrations were maintained after 2 years of treatment. Interpretation: These results support the long-term use of riociguat in patients with pulmonary arterial hypertension, and emphasise the prognostic value of 6MWD, WHO functional class, and NT-proBNP concentrations. Funding: Bayer Pharma AG.